2021
DOI: 10.1186/s13018-021-02732-8
|View full text |Cite
|
Sign up to set email alerts
|

Fibular osteotomy is helpful for talar reduction in the treatment of varus ankle osteoarthritis with supramalleolar osteotomy

Abstract: Background There have been debates on the necessity of fibular osteotomy (FO) in supramalleolar osteotomy (SMOT) for the treatment of varus ankle osteoarthritis. The purpose of the current study was to compare the clinical and radiological outcomes between SMOT with and without FO in the treatment of varus ankle osteoarthritis. Methods The SMOT group included 39 patients, and the SMOT with FO group included 24 patients. The basic information reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Our group has previ ously reported that the addition of medial distraction is helpful for the correction of increased talar tilt. 20,36 In the present SMOT cohort, patients with TT larger than 10 degrees had medial distraction. They appeared to do well, but further study is needed to verify this approach.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Our group has previ ously reported that the addition of medial distraction is helpful for the correction of increased talar tilt. 20,36 In the present SMOT cohort, patients with TT larger than 10 degrees had medial distraction. They appeared to do well, but further study is needed to verify this approach.…”
Section: Discussionmentioning
confidence: 82%
“…The indication and techniques of these additional procedures were described in our previous studies. 20,35,36 Also, we used medial distraction arthroplasty in 13 cases with preoperative TT angle larger than 10 degrees. The same senior surgeons performed the AA pro cedures.…”
Section: Operative Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Three o the 30 studies described two dierent patient cohorts in details that both met our inclusion criteria; Choi et al, 2021; patients 65 years o age or younger and patients older than 65 years [24]. Liang et al, 2021; patients treated with SMOT and patients treated with SMOT and bulotomy [37], Zhao et al, 2019; patients treated with SMOT and patients treated with SMOT and medial distraction arthroplasty (MDA) [42]. In total, 33 patient cohorts with 922 ankles were ound with a mean o 27.9 (SD 19.1) ankles (range 5 -99) per cohort.…”
Section: Study Characteristicsmentioning
confidence: 99%